The analysis and effectiveness verification of a chosen investment project: "Dust collector for the Anode Furnaces Department" KGHM Polska Miedź S.A. - Mroczek, Dawid (My University, 2012)
The design of the thesis leads from the overall perspective of the subject of investment projects through methods of their assessment up to a specific example. The most important element constitutes the positive evaluation of the investment project, regardless the selected version in the form of the modernization of the gas dedusting installation for the Anode Furnaces Department in Copper Smelter “Legnica”. To perform the analysis as detailed as possible – the use of both absolute (NPV, EVA) and relative (IRR, MIRR, CFROI) methods of investment project’s assessment was suggested. The primary source of information was the feasibility study of the project. Numbers of assumptions have been adopted in order to approach effects related to the project as appropriate as possible. References to more fully described in the literature of the subjects process of investment projects evaluation can be found in this paper. Moreover, to some extent the thesis deals with investment decisions, their determinants and the structure of assets and liabilities of enterprises. Not unrelated to the primary objective of this work are aspects of cost-cutting through environmental protection and improvement of labor working conditions. Therefore, further some information on this topic complements the frame work.
Analiza i weryfikacja efektywności wybranego projektu inwestycyjnego: "Odpylnia gazów dla Wydziału Pieców Anodowych" KGHM Polska Miedź S.A.
Keywords: projects assessment; investments valuation; Net Present Value (NPV); Internal Rate of Return (IRR); Modified Internal Rate of Return; Cash Flow Return on Investment; Economic Value Added (EVA)